2002
DOI: 10.1002/ijc.10146
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of colon cancer cells to long‐term 5‐fluorouracil exposure is correlated to the relative level of Bcl‐2 and Bcl‐XL in addition to Bax and p53 status

Abstract: Defects in apoptosis have been implicated in chemoresistance of colon cancer cells. We report here the ability to resist to 5-fluorouracil-induced apoptosis of 8 colon cancer cell lines differing in p53 and bax status: p53 ؊/0 bax ؉/؉ for TC7, SW480, HT-29; p53 ؉/؉ bax ؊/؊ for LS174T, LoVo; p53 ؉/؉ bax ؉/؊ for HCT116; p53 ؉/؉ or p53 ؉/0 bax ؉/؉ for LS513 or HCT-EB, respectively. To approximate to the in vivo therapy, the cell lines were exposed to a long-term treatment of 5-FU. The analysis of proteins implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
145
1
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(165 citation statements)
references
References 29 publications
11
145
1
3
Order By: Relevance
“…35 Other authors have demonstrated that resistance to long-term 5-FU exposure, was dependent not only on p53 status, but also on the levels of anti-and pro-apoptotic protein, such as Bax. 36 Our results show that combined treatment PBOX-15/5-FU is able to increase Bax levels, but the cleavage of caspase 3 was less than in the treatment with PBOX-15 alone.…”
Section: Discussionmentioning
confidence: 44%
“…35 Other authors have demonstrated that resistance to long-term 5-FU exposure, was dependent not only on p53 status, but also on the levels of anti-and pro-apoptotic protein, such as Bax. 36 Our results show that combined treatment PBOX-15/5-FU is able to increase Bax levels, but the cleavage of caspase 3 was less than in the treatment with PBOX-15 alone.…”
Section: Discussionmentioning
confidence: 44%
“…Evidence indicates that Bcl-2 and Bcl-XL act as stabilizers of mitochondrial membrane integrity by blocking the release of cytochrome c and subsequent caspase-9 and -3 activation, thus regulating the mitochondrial apoptotic pathway (Korsmeyer, 1992;Kluck et al, 1997;Martinou et al, 2000;Tsujimoto, 2000;. These effects comprise the main mechanism by which Bcl-2 and Bcl-XL inhibit the induction of apoptosis by a variety of chemotherapeutic agents hRFI enhances chemoresistance to 5-FU T Konishi et al including 5-FU (Miyashita and Reed, 1993;Reed et al, 1996;Nita et al, 2000;Sun et al, 2002;Violette et al, 2002). In compatible with this evidence, the present study has revealed that siRNA downregulation of either Bcl-2 or Bcl-XL prominently increases 5-FU-induced apoptosis, indicating that both Bcl-2 and Bcl-XL are crucial determinants of the apoptosis sensitivity towards 5-FU in HCT116 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the apoptosis regulators are known to be closely related to both chemosensitivity and prognosis in colorectal cancer (Kahlenberg et al, 2003). In particular, the expression of Bcl-2 family proteins is an important determinant of the chemosensitivity to 5-FU in colorectal cancer cells (Maurer et al, 1998;Ogura et al, 1999;Nita et al, 1998Nita et al, , 2000Violette et al, 2002). We have revealed in this study that hRFI overexpression in colorectal cancer cells elicits an increase of IC 50 values towards 5-FU as well as the specific upregulation of Bcl-2 and Bcl-XL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reportedly, bcl-XL protein is more crucial as an apoptosis-inhibiting factor than bcl-2 protein in colorectal cancer tissues (Maurer, Friess et al, 1998), and thus, is an important factor for the 5-FU resistance in colonic cancer cell lines (Nita, Nagawa et al, 1998, Nita, Ono-Nita et al, 2000, Violette, Poulain et al, 2002.…”
Section: Introductionmentioning
confidence: 99%